Trauma exposure and post-traumatic stress disorder within fire and emergency services in Western Australia - Skeffington, P.; Rees, Clare; Mazzucchelli, Trevor (John Wiley & Sons Ltd., 2016)
Objective: While it is widely accepted that fire and emergency work is of high risk for potentially traumatic event exposure and post-trauma pathology, there has been limited published data regarding Australian fire and emergency service workers. The relationship between trauma exposure and mental health outcomes, in particular the significance of social support and coping style was explored. Method: Participants were 210 Department of Fire and Emergency Services (DFES) career firefighters in Western Australia (WA). This study employed a cross-sectional, correlational design, with a combination of self-selection and random sampling. Results: Results found that DFES career members were exposed to trauma at significantly higher rates than the general population and reported elevated rates of post-traumatic stress disorder (PTSD) symptomatology. Trauma exposure, social support, and coping style significantly contributed to variation in PTSD symptomatology, with maladaptive coping strategies accounting for more PTSD variance than adaptive coping. Conclusions: Elevated rates of PTSD identify WA DFES members as a high risk population. There was evidence that trauma exposure, social support, and coping style significantly contributed to levels of PTSD symptomatology. Maladaptive coping strategies, such as distraction, substance use, venting and self-blame, accounted for more variance in PTSD symptomatology than adaptive coping strategies, indicating that prevention or treatment interventions may be most effective by targeting reduction of maladaptive coping strategies, with a secondary focus on building adaptive coping strategies.